2017
DOI: 10.1007/s40808-017-0364-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological carrying capacity of public green spaces as a sustainability index of urban population: a case study of Mashhad city in Iran

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The spatial analysis of urban topography in geographical information system (GIS) indicated that the mean elevation values vary between 920 and 1340 m above sea level in northeast and southwest, respectively. In recent years, Mashhad city has been considered as an exciting research case of development modeling such as simulating urban growth (Rafiee et al 2009), building height construction modeling (Mansouri Daneshvar et al 2017a), carrying capacity of urban green spaces (Mansouri Daneshvar et al 2017b), urban transportation modeling (Bikdeli et al 2017), urban sprawl modeling (Rabbani et al 2017), and urban flexibility (Sarvari and Esnaashari 2018). Besides, the present paper focuses on hybrid modeling to assess the sprawl effects on climate parameters.…”
Section: Study Areamentioning
confidence: 99%
“…The spatial analysis of urban topography in geographical information system (GIS) indicated that the mean elevation values vary between 920 and 1340 m above sea level in northeast and southwest, respectively. In recent years, Mashhad city has been considered as an exciting research case of development modeling such as simulating urban growth (Rafiee et al 2009), building height construction modeling (Mansouri Daneshvar et al 2017a), carrying capacity of urban green spaces (Mansouri Daneshvar et al 2017b), urban transportation modeling (Bikdeli et al 2017), urban sprawl modeling (Rabbani et al 2017), and urban flexibility (Sarvari and Esnaashari 2018). Besides, the present paper focuses on hybrid modeling to assess the sprawl effects on climate parameters.…”
Section: Study Areamentioning
confidence: 99%
“…Our study found that the most frequent node was sustainable development, with an appraisal rate of 238. Other indicators were as follows: resource and environment constraints, infrastructure, ecological civilization, urban security, public services, science and technology, and social culture [8,15,20,23,25]. Table 2 revealed the nodes of urban comprehensive carrying capacity, which consists of the elements related to urban comprehensive carrying capacity.…”
Section: Methodsmentioning
confidence: 99%
“…The ecosystem is close to the system of human society, but the study of this system is still in the early stages. The ecologic carrying capacity emphasizes the effect of the constraints and the support of resources on the urban carrying capacity [20]. The carbon footprint is an effective tool to explore the ecologic carrying capacity, and has also been adopted in numerous studies [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Cf 3 soil erosion factor was considered based on the extension of geological units (GSI 2015). Usually, the corrective factor for igneous rocks was assumed as 1 (without limitation) while for sandstone, limestone, alluvial and shale/marl units, the corrective factors considered as 0.9, 0.85, 0.8 and 0.75, respectively (Mansouri Daneshvar et al 2017b). Hence, this factor was considered as 0.8 on average for the whole study area.…”
Section: Real Carrying Capacity (Rcc)mentioning
confidence: 99%